ANALISIS BIBLIOMETRIK TERHADAP TREND RISET “HALAL TOURISM” MENGGUNAKAN VOSVIEWER - Widiastiana Vista Wijaya; Citra Puspa Maulidina; Shilvy Andini Sunarto; Siti Zulzilah (Asosiasi Dosen Muda Indonesia, 2023)
The aim of bibliometric analysis is mapping research trends by processing metadata from Google Scholar. This research also wants to know the research trend on